Penguatan Identitas dan Daya Tarik Wisata Bukit Waruwangi Melalui Rancangan Desain Maskot dan Logo Merchandise - Hafizh, Sulthan; Gumelar, Rangga Galura (Kinesik, 2024)
Tourism is one of the economic sectors that has great potential in increasing regional and national income. Bukit Waruwangi tourist attraction located in Serang Regency, Banten Province has great potential to attract both domestic and foreign tourists who contribute directly to the economy through various sectors such as accommodation, transportation, and culinary. Therefore, in the increasingly fierce competition in the tourism industry, an effective marketing strategy is needed to increase the attractiveness and visibility of a tourist attraction, through designing a mascot visual design as a strengthening identity that can be applied to various merchandise.